2009
DOI: 10.1111/j.1442-2042.2009.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical prostatic protrusion predicts clinical progression of benign prostatic enlargement in patients receiving medical treatment

Abstract: Objectives: To assess intravesical prostatic protrusion (IPP) as a novel predictor of clinical progression in patients with benign prostatic enlargement (BPE). Methods: All patients attending the outpatient clinic at our institution who were being treated for lower urinary tract symptoms (LUTS) secondary to BPE between January 1997 and December 2003 were recruited into the study. International Prostate Symptom Score (IPSS) scores, uroflowmetry parameters, post-void residual urine volume (PVR), IPP and serum pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 16 publications
2
55
1
1
Order By: Relevance
“…Although there are other studies 22,23 suggesting that IPP might predict clinical progression in LUTS and/or BPE, there is no specific study of patients under combination therapy with histological examinations. Thus, the present study has apparently revealed that the treatment protocol in cases with severe IPP tends to be converted to surgical intervention and has also suggested that administration of dutasteride from the early stage of LUTS and/ or BPE might be preferable.…”
Section: Commentmentioning
confidence: 97%
“…Although there are other studies 22,23 suggesting that IPP might predict clinical progression in LUTS and/or BPE, there is no specific study of patients under combination therapy with histological examinations. Thus, the present study has apparently revealed that the treatment protocol in cases with severe IPP tends to be converted to surgical intervention and has also suggested that administration of dutasteride from the early stage of LUTS and/ or BPE might be preferable.…”
Section: Commentmentioning
confidence: 97%
“…Patients with Grade 3 IPP were more likely to have clinical deterioration compared to those with Grade 1 IPP (44% vs. 6%) at a mean follow-up period of 32 months. (14) Not all patients with Grade 3 IPP progress, so further management of BPH should be based on the severity of the disease, which can be classified according to the staging system (Table I). (15) Disease severity is based on the presence or absence of significant prostatic obstruction (that impairs either the emptying or storage functions of the bladder) and the presence or absence of bothersome symptoms (quality of life [QOL] score ≥ 3).…”
Section: Pathophysiology Of Bphmentioning
confidence: 99%
“…Lee et al showed that men with Grade 3 IPP who are on medical management are sevenfold more likely to progress over a mean follow-up period of 32 months [ 12 ].…”
Section: Intravesical Prostatic Protrusionsmentioning
confidence: 99%